Evaluating the implementation of a digital coordination centre in an Australian hospital setting: a mixed method study protocol - Timothy N Fazio; Daniel Capurro; Colin Malone; Sam Freeman; Wynona Black; Wendy W Chapman; Jana Gazarek; Meredith J Layton; Kayley Lyons; Laura Pumo; Samantha Plumb; Brad Astbury (BMJ Health & Care Informatics)
Introduction This protocol outlines a mixed methods study evaluating a new Digital Coordination Centre (DCC) at the Royal Melbourne Hospital (RMH), Melbourne, Australia. While coordination centres show potential for impact, evidence on effective implementation in the Australian context remains scarce. This study aims to address this gap.Methods and analysis The evaluation involves a two-stage approach: a process evaluation to clarify DCC design and identify implementation factors, and an initial outcome evaluation to assess short and medium term outcomes. A developmental approach will support continuous improvement, and implementation science theories applied to unpack change processes. Data sources will include interviews, project documentation and observations, with qualitative and quantitative analyses targeting metrics like emergency department boarding and length of stay.Ethics and dissemination This study has been approved by the RMH Human Research Ethics Committee (QA2023089). Findings will be shared through peer-reviewed publications and conference presentations.